2016
DOI: 10.1038/srep29888
|View full text |Cite
|
Sign up to set email alerts
|

Novel avian influenza A (H5N6) viruses isolated in migratory waterfowl before the first human case reported in China, 2014

Abstract: In May 2014, China formally confirmed the first human infection with the novel H5N6 avian influenza virus (AIV) in Sichuan Province. Before the first human case was reported, surveillance of AIVs in wild birds resulted in the detection of three H5N6 viruses in faecal samples from migratory waterfowl in Chenhu wetlands, Hubei Province, China. Genetic and phylogenetic analyses revealed that these three novel viruses were closely related to the H5N6 virus that has caused human infections in China since 2014. A Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 58 publications
(61 reference statements)
2
52
0
Order By: Relevance
“…Previous studies revealed that the HPAI H5N6 virus contained the hemagglutinin (HA) gene of H5 clade 2.3.4.4, the internal genes of H5 clade 2.3.2.1, and the NA gene from the H6N6 avian virus (9,12,13). Based on the genetic evidence, HPAI H5N6 virus likely originated from migratory waterfowl (14). Further reassortment with other avian influenza viruses generated multiple genotypes of HPAI H5N6 viruses (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies revealed that the HPAI H5N6 virus contained the hemagglutinin (HA) gene of H5 clade 2.3.4.4, the internal genes of H5 clade 2.3.2.1, and the NA gene from the H6N6 avian virus (9,12,13). Based on the genetic evidence, HPAI H5N6 virus likely originated from migratory waterfowl (14). Further reassortment with other avian influenza viruses generated multiple genotypes of HPAI H5N6 viruses (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…with lower but increased affinity for the human-like receptor (␣-2,6 sialic acid) (14,39,40). The mutations identified in human isolates (S123P, I151T, T156A, and the deletion at position 126 in HA) should be further investigated to identify their effects on the receptor binding preferences of H5N6 viruses.…”
mentioning
confidence: 99%
“…Recently, with more H5N6 genomes sequenced, it has become clear that the gene segments of these viruses derived from a variety of AIV subtypes. Specifically, the PB2 gene of some H5N6 AIVs derived from that of H6N6 viruses, while the PB1 gene originated in H3 subtype viruses (9); a novel H5N6 virus isolated from migratory waterfowl possessed a hemagglutinin (HA) gene that was related to that of H5N2 viruses (10); the internal genes of viruses isolated from two human cases in 2015 derived from H7N9/H9N2 viruses in chickens (11); human infections in Guangdong Province, China, in 2015 were due to a newly emerged H5N6 virus that was a reassortant between H6N6 and H9N2 viruses (12); and a human-associated H5N6 (clade 2.3.3.4) virus sampled in China during 2014 to 2015 was a triple reassortant derived from H6N6, H5N1 (clade 2.3.1.1), and H5N6 (2.3.4.4) viruses (13). In addition, a recent study of multiple live poultry markets (LPMs) in southern China revealed that the HA gene of H5N6 viruses derived from clade 2.3.4.4, the NA gene derived from H6N6 viruses, and all six internal gene segments had their origins in clades 2.3.4.4 and 2.3.2.1 of H9N2/H7N9 viruses (14).…”
mentioning
confidence: 99%
“…Two types of A(H5N6) can be distinguished based on the length of NA: with-and without truncated NA stems (deletions at amino acid positions 59-69), a signature of adaptation to terrestrial poultry ( (Bi et al, 2016;Sun et al, 2016;Yang et al, 2017).…”
Section: Ii) Molecular Marker Analysismentioning
confidence: 99%